Theoretical and Simulation Based Approach for Controlling Aircraft Longitudinal and Lateral Yaw Damper Movement Using PID Controller - Dahiya, R; Singh, AK (International Journal of Computer Sciences and Engineering, 2025)
In this manuscript we consider two different parameters of DC-8 aircraft and extend the work as original research for controlling the longitudinal and lateral yaw damper movement. Here we consider both the theoretical and numerical aspect of aircraft dynamics by modeling the control surfaces i.e., elevators and lateral yaw damper. For controlling these control surfaces we design an intelligent PID controller and examine the overall performance of the system primarily based on time response specification. The simulation results generated are plotted and evaluated between controller response v/s deflection of control surfaces i.e., horizontal stabilizer and vertical stabilizer/rudder. The controller is designed based on dynamical model of aircraft for which equations are derived governing input to elevator, and rudder, which are used to control aircraft longitudinal and directional stability of aircraft. A quantitative analysis of PID controller has been carried out in MATLAB 2014a Simulink© environment for all the two movements of aircraft based on time response specification.